PERANCANGAN DIRECT CHARGING SEPEDA MOTOR LISTRIK DAN PEMILIHAN LOKASI PEMASANGAN DI BALI SELATAN - I N. A. P. Putra; I W. Sukerayasa; W. G Ariastina; I N. S. Kumara; I N. Setiawan; I. A. D. Giriantari; D. A. S. Santiari (Jurnal SPEKTRUM, 2025)
Bali is one of the regions in Indonesia at the forefront of the transition toward clean energy. One of the key steps to achieving this goal is the shift to electric vehicles (EVs). Therefore, the design of electric vehicle charging stations is a crucial factor in ensuring a smooth transition. Charging stations must be strategically located to provide easy access for users, and their planning must comply with existing regulations. One type of charging station is the Public Electric Vehicle Charging Station (SPKLU). However, most SPKLUs are focused on electric cars, whereas the use of electric motorcycles is far more widespread. For this reason, this study focuses on the design of a direct charging system for electric motorcycles, which can be connected directly to the vehicles. The design process includes both 3D modeling and the electrical layout. The selection of a suitable location will be carried out using the Analytic Hierarchy Process (AHP) to determine the optimal site in the South Bali area